Cannabis Withdrawal, Posttreatment Abstinence, and Days to First Cannabis Use Among Emerging Adults in Substance Use Treatment: A Prospective Study. (January 2016) - Davis, Jordan P.; Smith, Douglas C.; Morphew, Jason W.; Lei, Xinrong; Zhang, Saijun
Very little prospective research investigates how cannabis withdrawal is associated with treatment outcomes, and this work has not used the Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5 ) thresholds for cannabis withdrawal. The sample included 110 emerging adults entering outpatient substance use treatment who were heavy cannabis users with no other drug use and limited alcohol use. We used survival analyses to predict days to first use of cannabis and logistic regression to predict whether participants were abstinent and living in the community at 3 months. Those meeting criteria for cannabis withdrawal were more likely to return to use sooner than those not meeting criteria for cannabis withdrawal. However, the presence of cannabis withdrawal was not a significant predictor of 3-month abstinence. Emerging adults with DSM-5 cannabis withdrawal may have difficulty initiating abstinence in the days following their intake assessment, implying the need for strategies to mitigate their more rapid return to cannabis use.